The Effect of Liquidity Ratio and Solvency Ratio on the Profitability of Plantation Subsector Companies Listed on the Indonesian Stock Exchange - Refni sukmadewi; Dewi Sartika; Mulyani Rodi Muin; Deviana Sofyan (Husnayain Business Review, 2021)
This study was conducted to determine the effect of liquidity and solvency on profitability in plantation sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2020 because it often happens that companies are unable to balance their liquidity and solvency positions because the target company is pursuing profits without compensating management in terms of the ability to pay the debt.This study uses multiple regression analysis with a significance of 0.05. Liquidity variable is measured using current ratio, solvency is measured by debt ratio, while profitability is measured by return on assets. The sampling method used is purposive sampling method. The results partially show that liquidity has a significant effect on profitability, while solvency also has a significant effect on profitability and has a significant effect on profitability. Simultaneously liquidity and solvency have a significant effect on profitability.